2019
DOI: 10.3390/f10010066
|View full text |Cite
|
Sign up to set email alerts
|

Excess Nitrogen in Temperate Forest Ecosystems Decreases Herbaceous Layer Diversity and Shifts Control from Soil to Canopy Structure

Abstract: Research Highlights: Excess N from atmospheric deposition has been shown to decrease plant biodiversity of impacted forests, especially in its effects on herbaceous layer communities. This work demonstrates that one of the mechanisms of such response is in N-mediated changes in the response of herb communities to soil resources and light availability. Background and Objectives: Numerous studies in a variety of forest types have shown that excess N can cause loss of biodiversity of herb layer communities, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 49 publications
1
15
0
Order By: Relevance
“…For nitrogen deposition, we expected two counteracting effects: a positive effect on understorey biomass (as found, e.g., by Gilliam () for cover) as a result of increasing soil nitrogen availability (Falkengren‐Grerup, Brunet, & Diekmann, ) and a negative effect as a result of increasing overstorey biomass reducing light availability (Hyvönen et al, ; Reyer, ). Neither of those was detected in our analysis.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…For nitrogen deposition, we expected two counteracting effects: a positive effect on understorey biomass (as found, e.g., by Gilliam () for cover) as a result of increasing soil nitrogen availability (Falkengren‐Grerup, Brunet, & Diekmann, ) and a negative effect as a result of increasing overstorey biomass reducing light availability (Hyvönen et al, ; Reyer, ). Neither of those was detected in our analysis.…”
Section: Discussionmentioning
confidence: 74%
“…Most of these responses are, however, context‐dependent. Whether or not the understorey reacts to global change often depends on local site conditions, defined by the overstorey and the soil (Chen, Biswas, Sobey, Brassard, & Bartels, ; Gilliam, ; Kim et al, ; Perring, Diekmann, et al, ; Verheyen et al, ). Nitrogen deposition has, for example, the potential to decrease species richness in the understorey by stimulating competitive exclusion (Gilliam, ), but this response is often not generalizable (Perring, Diekmann, et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…While moisture and nitrogen appeared to be independent co‐limiting resources, we did not find any discernible role of canopy openness on the functional composition and diversity of understorey plant communities. Light tends to be a more important factor in plant community assembly when below‐ground resources are in greater supply (DeMalach, Zaady, & Kadmon, ; Gilliam, ).…”
Section: Discussionmentioning
confidence: 99%
“…Functional diversity also changes along resource gradients (Schellenberger Costa et al, ), but the nature of the relationship between functional diversity and resource availability is variable. Some studies have found that functional diversity decreases with increasing resource availability (trait convergence) as species that thrive in low resource conditions are out‐competed (Eskelinen & Harrison, ; Gilliam, ; Harpole & Suding, ). Others have found that functional diversity increases with increasing resource availability (trait divergence) as species with more diverse strategies can fill a larger niche space (Bernard‐Verdier et al, ; Jacobs et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…A large body of research over the past decade demonstrates that the understory herb layer exhibits strong temporal dynamics [5]. These dynamics have typically been attributed to several different anthropogenic drivers, including changes in light conditions due to forest management [6], nitrogen deposition [7][8][9], climate change [10,11], and excessive deer browsing [12,13].…”
Section: Introductionmentioning
confidence: 99%